STUDI OPTIMALISASI TEMPAT PEMROSESAN AKHIR (TPA) SANGGRAHAN KECAMATAN KRANGGAN, KABUPATEN TEMANGGUNG JAWA TENGAH - Melky Sidik M. Hutauruk (Jurnal Teknik Lingkungan, 2012)
Sanggrahan landfill is a final processing contained in Temanggung County and is located in the village district Sanggrahan Kranggan with ± 2.6 ha of land. Existing condition Sanggrahan landfill has 2 zones of active landfill conditions now beginning to fill because the garbage has already reached 80%. The condition is caused by the use of the concept of waste management at the Sanggrahan landfill still use the concept of Controlled Landfill. The limited land, and reduction and infrastructure support in the landfill resulted in less optimal waste management, so that it will cause a negative impact on the environment around the landfill. This is the main problem with increasing waste generation from population growth and has not found new land instead. To reduce the negative impact and optimizing available landfill and extend the use of the landfill, it is necessary to waste management with the concept of Sanitary Landfill, and the addition of landfill infrastructure.